Analisis Pengaruh Beban Kerja Dan Technostressterhadap Kinerja Karyawan Dengan Motivasi Sebagaivariabel Intervening Pada Rumah Sakit Jiwa Prof. Dr. HB Saanin Padang - Zahra Khairina; Vicky Brama Kumbara; Nia Nadilla (Jurnal Ekonomi dan Bisnis Digital, 2026)
This study aims to analyze the effect of workload and technostress on employee performance with work motivation as an intervening variable at Prof. Dr. HB Saanin Mental Hospital, Padang. This research was motivated by fluctuations in organizational performance achievement, increasing demands for mental health services, and the implementation of hospital digital systems that potentially create technology-based work pressure. This study employed a quantitative approach using a survey method. The population consisted of all employees at Prof. Dr. HB Saanin Mental Hospital, Padang, with a total sample of 80 respondents selected through purposive sampling technique. Data were collected through questionnaires and analyzed using Structural Equation Modeling (SEM) based on Partial Least Square (PLS). The results indicate that: (1) workload has a positive and significant effect on employee performance, (2) workload has a positive and significant effect on work motivation, (3) technostress has no significant effect on employee performance, (4) technostress has no significant effect on work motivation, (5) work motivation has a positive and significant effect on employee performance, (6) work motivation is able to mediate the effect of workload on employee performance, and (7) work motivation is not able to mediate the effect of technostress on employee performance. These findings suggest that workload management and enhancement of work motivation are crucial factors in improving employee performance in mental hospitals, while technostress was not proven to have a significant influence in this study.